2012
DOI: 10.1128/jvi.05957-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Severe Acute Respiratory Syndrome Coronavirus Pathogenesis and Virulence in Young and Aged Mouse Models of Human Disease

Abstract: SARS coronavirus (SARS-CoV) causes severe acute respiratory tract disease characterized by diffuse alveolar damage and hyaline membrane formation. This pathology often progresses to acute respiratory distress (such as acute respiratory distress syndrome [ARDS]) and atypical pneumonia in humans, with characteristic age-related mortality rates approaching 50% or more in immunosenescent populations. The molecular basis for the extreme virulence of SARS-CoV remains elusive. Since young and aged (1-year-old) mice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(174 citation statements)
references
References 75 publications
6
168
0
Order By: Relevance
“…Two of these changes are in residues of the receptor binding motif that interacts with ACE2 and, as predicted by structural modeling, may enhance binding to murine ACE2 (Day et al, 2009;Frieman et al, 2012). Adaptation of the spike glycoprotein to bind more efficiently to ACE2 proteins of different species is thought to be critical for changes in the host range and tissue tropism of SARS-CoV (Becker et al, 2008;Frieman et al, 2012;Li, 2008;Sheahan et al, 2008). We observed that primary murine ATI-like cells were not susceptible to infection by v2163, so ACE2 expression by these cells was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these changes are in residues of the receptor binding motif that interacts with ACE2 and, as predicted by structural modeling, may enhance binding to murine ACE2 (Day et al, 2009;Frieman et al, 2012). Adaptation of the spike glycoprotein to bind more efficiently to ACE2 proteins of different species is thought to be critical for changes in the host range and tissue tropism of SARS-CoV (Becker et al, 2008;Frieman et al, 2012;Li, 2008;Sheahan et al, 2008). We observed that primary murine ATI-like cells were not susceptible to infection by v2163, so ACE2 expression by these cells was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Human isolates of SARS-CoV do not cause lethal disease in mice, but acquire virulence upon serial passage in mice (Day et al, 2009;Roberts et al, 2007). These mouse-adapted isolates are used to study the mechanisms of SARS-CoV pathogenesis in vivo (Frieman et al, 2012). v2163 is an isolate of SARS-CoV that was passaged 25 times in the lungs of BALB/c mice and causes a highly lethal pulmonary infection in mice (Day et al, 2009).…”
Section: Phenotypes Of Primary Alveolar Epithelial Cellsmentioning
confidence: 99%
“…A standard procedure was the adaptation of SARS-CoV and MERS-CoV to grow in mice and reproduce the disease caused in humans. This strategy was directly applied in the case of SARS-CoV using conventional mouse strains without the need for Tg mice expressing the human ACE2 receptor (Day et al, 2009;Frieman et al, 2012;Roberts et al, 2007). Mouse-adapted SARS-CoV obtained by passing the virus 15 times in mice (SARS-CoV-MA15) has been an excellent model as it reproduces very well the pathology caused by SARS-CoV in humans, including mortality (DeDiego et al, 2011(DeDiego et al, , 2014b.…”
Section: Animal Models For Cov Vaccine and Antivirals Studiesmentioning
confidence: 99%
“…To improve vaccine efficacy, we engineered and adapted rSARS-CoV to efficiently grow in mice (rSARS-CoV-MA15). To this end, we incorporated six nucleotide substitutions into the SARS-CoV genome (Frieman et al, 2012;Roberts et al, 2007) using our reverse-genetics system based on bacterial artificial chromosomes. Using the rSARS-CoV-MA as a backbone genome, a second set of E-deletion vaccine candidates was generated (Fett et al, 2013).…”
Section: Sars-cov Genes As Modulators Of the Innate Immune Responsementioning
confidence: 99%
“…The functional receptors for SARS coronavirus are angiotensin receptor enzyme 2 (ACE-2) and CD209L. 107,108 Autopsy studies of patient who have died of SARS show that the lung and intestinal tract are the primary sites of infection. 109 Lung histology often shows diffuse alveolar damage with varying degrees of organization.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%